Analysis of E-Banking Development In Islamic and Conventional Commercial Banks: Evidence From Indonesia - Pujiharto, Yaya Ruhenda Casmita; Yusnita, Titien (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2024)
This study analyzes the impact of IT-based banking services on Islamic and Conventional Commercial Banks in Indonesia. It evaluates their influence on the number of bank branches, Automated Teller Machines (ATM), Operating Costs (BOPO), and Net Income (NI). The research uses secondary data from The Financial Services Authority (OJK), Bank Indonesia, and the Indonesian Payment System Association (ASPI) for the 2018-2023 period. The data analysis employs the ECM (Error Correction Model) method. Results show that e-banking services significantly affect the dependent variables. For the branch model, mobile and internet banking impact branch numbers in the long term, but not in the short term. Mobile and internet banking have a long-term effect on ATMs, while the Quick Response Code Indonesian Standard (QRIS) and e-banking services influence ATMs in the short term. In terms of BOPO, mobile banking and QRIS affect it in the long term, while internet banking and QRIS influence it in the short term. Lastly, mobile banking and QRIS have a long-term effect on Net Interest Margin (NIM), but no significant effect in the short term. Overall, the findings demonstrate that mobile banking, internet banking, and QRIS are important factors influencing various banking metrics over different timeframes.